2019
DOI: 10.1001/jamanetworkopen.2019.8398
|View full text |Cite
|
Sign up to set email alerts
|

Global Incidence of Frailty and Prefrailty Among Community-Dwelling Older Adults

Abstract: IMPORTANCE Frailty is a common geriatric syndrome of significant public health importance, yet there is limited understanding of the risk of frailty development at a population level. OBJECTIVE To estimate the global incidence of frailty and prefrailty among community-dwelling adults 60 years or older.DATA SOURCES MEDLINE, Embase, PsycINFO, Web of Science, CINAHL Plus, and AMED (Allied and Complementary Medicine Database) were searched from inception to January 2019 without language restrictions using combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
266
5
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(292 citation statements)
references
References 117 publications
(158 reference statements)
8
266
5
13
Order By: Relevance
“…Frailty is difficult to diagnose, particularly within intensive care settings, due to its coexistence with other agerelated conditions and because of the lack of a universally accepted clinical definition [5]. Sarcopenia, or age-related loss of skeletal muscle and muscle strength, is a key physical component of frailty.…”
Section: Introductionmentioning
confidence: 99%
“…Frailty is difficult to diagnose, particularly within intensive care settings, due to its coexistence with other agerelated conditions and because of the lack of a universally accepted clinical definition [5]. Sarcopenia, or age-related loss of skeletal muscle and muscle strength, is a key physical component of frailty.…”
Section: Introductionmentioning
confidence: 99%
“…Frailty is a clinical status and a multidimensional syndrome characterized by the loss of physiologic and cognitive reserves. 1,2 Although the assessment of frailty is challenging, [3][4][5] there are two major approaches to its measurement: the phenotypic frailty model and the frailty index of de cit accumulation. 6 The phenotypic frailty model focuses predominantly on physical symptoms, such as weight loss, exhaustion, weakness, slowness, and reduced physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Women tend to have a higher incidence of frailty than men [48,49], and it was suggested that this might be attributable to both biological and socioeconomic factors [50]. Studies have shown that loneliness is strongly associated with adverse health conditions in men and women [51,52].…”
Section: Introductionmentioning
confidence: 99%